(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Heart diseases have a large share amongst non-communicable diseases. India is currently heading towards becoming a heart disease capital of world. This puts a tremendous pressure on available resources of medical and surgical management. Thus, it would be a great asset if these diseases could be managed through traditional system of medicine like Ayurveda. According to latest data of American Heart Association, cardiovascular disease including heart attack and stroke remain the No. 1 killer of men and women causing 36 percent of all the deaths per year. Changes in diet pattern, dietary habits and lifestyle, certain social and environmental changes have led to us in the era of hypertension, hyperlipidemia, obesity, cardiac diseases and many more diseases. There are a number of drugs and medicinal preparations described in the texts of Ayurveda like Arjuna, Tagara, Haritaki, Tambula, Brahmi etc, having wonderful effects in CVD. Various techniques of Yoga, Pranayama (breathing practices), spiritual upliftment are having excellent preventive and therapeutic effects on anxiety, hypertension etc. which are main risk factors of heart disorders.